TINJAUAN WAKTU PENYEDIAAN DOKUMEN REKAM MEDIS PASIEN RAWAT JALAN POLI DALAM - Syifa Sherina Kiswari (Poltekkes 'Aisyiyah Banten, 2022)
Objectives: To find out the description of the Time of Providing Medical Record Documents for Outpatient Polyclinic Patients at Tk Hospital. IV Kencana Attack in 2022. Methodology: This research uses descriptive research with interview and observation methods. The subjects in this study were 6 people consisting of the head of the medical record, the medical record coordinator, the filing officer, the receiving/returning medical record document, the medical record distribution officer and the registration officer, and the object of this study was the patient's medical record document. outpatients borrowed from the inner poly with the average number of medical record documents borrowed per day is 20 medical record documents. The research instrument used observation sheets, interview guidelines, stopwatches, and recorders. Results: As many as 13 officers who play a role in providing outpatient medical record documents, only 1 has a D3 Medical Record and Health Information educational background. Standard Operating Procedures related to the Provision of Outpatient Medical Record Documents are not yet owned. As many as 81 medical record documents were observed, medical record documents that were in accordance with the SPM (≤10 minutes) were 39 (48%) with an average time of providing medical record documents of 8 minutes, while the number of medical record documents that were not in accordance with the SPM (>10 minutes) as many as 42 (52%) with an average time of providing medical record documents 14 minutes 12 seconds.